Public Intention to Use Reusable Menstrual Products and Their Impact on Menstrual Pads Waste Reduction in Dki Jakarta - Zahira, Cletra Halla; Widyarsana, I Made Wahyu; Rachmatiah , Indah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Single-use menstrual waste is a serious issue since they consist of ingredients that make it difficult to biodegrade and are contaminated with blood and other bodily fluids, that could possibly contaminate other waste. Most women in DKI Jakarta still use single-use menstrual pads despite the availability of reusable alternatives. With the Theory of Planned Behavior, this study analyzed factors that affects intention to use reusable menstrual products, as well as the possible waste generation from various menstrual products and reccomendations for their management in DKI Jakarta. This study applied quantitative methods using online survey to 448 participants. Factors that positively influence intention to use reusable menstrual products are Subjective norm, Perceived behavioral control, and Attitude (sig. < 0.05), while Knowledge has no significant influence (sig. > 0.05). Attitude is the factor with most contribution (sig. < 0.001) with highest beta value of 0,415. DKI Jakarta could potentially generate 42,072,587.52 kg/year of menstrual pads waste; 73.91 kg/year of menstrualcups waste; and 4,909.08 kg/year of reusable pads waste. Recommendations given are the shifting of single-use menstrual products users to reusable menstrual products to reduce single-use menstrual products waste and improving the waste management system for single-use menstrual pads waste in DKI Jakarta